Palmitate Activates Autophagy in INS-1E β-Cells and in Isolated Rat and Human Pancreatic Islets - Martino, Luisa; Masini, Matilde; Novelli, Michela; Beffy, Pascale; Bugliani, Marco; Marselli, Lorella; Masiello, Pellegrino; Marchetti, Piero; De Tata, Vincenzo (PLOS ONE, 2012)
We have investigated the in vitro effects of increased levels of glucose and free fatty acids on autophagy activation in pancreatic beta cells. INS-1E cells and isolated rat and human pancreatic islets were incubated for various times (from 2 to 24 h) at different concentrations of glucose and/or palmitic acid. Then, cell survival was evaluated and autophagy activation was explored by using various biochemical and morphological techniques. In INS-1E cells as well as in rat and human islets, 0.5 and 1.0 mM palmitate markedly increased autophagic vacuole formation, whereas high glucose was ineffective alone and caused little additional change when combined with palmitate. Furthermore, LC3-II immunofluorescence co-localized with that of cathepsin D, a lysosomal marker, showing that the autophagic flux was not hampered in PA-treated cells. These effects were maintained up to 18–24 h incubation and were associated with a significant decline of cell survival correlated with both palmitate concentration and incubation time. Ultrastructural analysis showed that autophagy activation, as evidenced by the occurrence of many autophagic vacuoles in the cytoplasm of beta cells, was associated with a diffuse and remarkable swelling of the endoplasmic reticulum. Our results indicate that among the metabolic alterations typically associated with type 2 diabetes, high free fatty acids levels could play a role in the activation of autophagy in beta cells, through a mechanism that might involve the induction of endoplasmic reticulum stress.